(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
In this paper, we discuss the representations of Black masculinities in the semiotic expressions of the Natura brand on its Instagram account, through a semiotic analysis of content posted between 2018 and 2020. Based on the observation of a corpus composed of 83 posts, analyzed from an intersectional perspective and Peircean semiotics, we articulate theoretical references on advertising and consumption, race studies, and studies on men and masculinities. The analyses indicate an underrepresentation of Black men, who rarely appear as consumers of the brand, while also pointing to resignifications and reiterations of meanings related to Black masculinities in themes such as sexuality, work, care, affection, and fatherhood.